Kemampuan Guru PAI Dalam Menyusun Instrumen Penilaian Keterampilan Berkomunikasi Sesuai IASP 2020 - Siti Rohmah Kurniasih; Rina Nur Azizah; Siti Rohmah Maulidah; Mulyawan Safwandy Nugraha; Ade Yeti Nuryantini (Indonesia, 2023)
This study aims to identify the ability of PAI teachers to develop instruments for assessing students' communication skills according to IASP 2020 so that assessments can be carried out in a more objective manner, are able to measure students' communication abilities appropriately, and have an impact on the quality of the learning process. The research method used is quantitative, and the type of research is survey research. The data sources used include primary data sources obtained from 17 teachers at Subrayon 02 SMP level. The research sources consist of secondary research sources, which come from archives, documents, books, and journals that are relevant to the research problem formulation. Data collection techniques used questionnaires distributed using Google Forms. Then the data were analyzed using descriptive statistics. The results of the study showed that the ability of PAI teachers to compile instruments for assessing students' communication skills orally was 74.63% and 65.07% in writing, so both of them fall into the fairly good category.